2009
DOI: 10.1007/s12583-009-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Features of late cenozoic deepwater sedimentation in southern Qiongdongnan Basin, northwestern South China Sea

Abstract: Based on high resolution 2D and 3D seismic data acquired in recent years, using sequence stratigraphy analysis and geophysical methods, we discuss the features of Late Cenozoic deepwater sedimentation in the southern Qiongdongnan (琼东南) basin. The study area entered a bathyal slope environment in the Miocene. The channel developed in the Sanya (三亚) Formation was controlled by a fault break, and its shingled seismic characteristics represent multiple erosion and fill, which may indicate that turbidite current de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…They found that in the BYS a strong post-rifting acceleration of subsidence occurred at 17.5-15.5 Ma accompanied by a sudden shift of depocenter, which might be caused by an important tectonic event. Yuan et al (2009) presented 2D and 3D seismic data showing features of the deepwater sedimentation in the Qiongdongnan basin, including sinuous turbidity channels and polygonal faults. Sun Q L et al (2009) demonstrated that the development of polygonal faults in Miocene formations of this basin might be triggered by over-pressure pore fluid which is restricted in the fine-grained sediments of bathyal facies.…”
Section: Basins and Hydrocarbon In The South China Seamentioning
confidence: 99%
“…They found that in the BYS a strong post-rifting acceleration of subsidence occurred at 17.5-15.5 Ma accompanied by a sudden shift of depocenter, which might be caused by an important tectonic event. Yuan et al (2009) presented 2D and 3D seismic data showing features of the deepwater sedimentation in the Qiongdongnan basin, including sinuous turbidity channels and polygonal faults. Sun Q L et al (2009) demonstrated that the development of polygonal faults in Miocene formations of this basin might be triggered by over-pressure pore fluid which is restricted in the fine-grained sediments of bathyal facies.…”
Section: Basins and Hydrocarbon In The South China Seamentioning
confidence: 99%
“…The surrounding areas could have acted as source areas for the sediment supply into the study area during Cenozoic time (Yao et al, 2008). The QDNB is located in the western part of the South China Sea, which is basically composed of 2 mega sequences: the first represents the rifting period (53.5-23.3 Ma) and the second represents the post-rifting period (23.3 Ma to Quaternary) Yuan et al, 2009b) (Fig. 2).…”
Section: Geological Settingmentioning
confidence: 99%
“…2). The shelf-slope system of NSCS started to develop during the middle Miocene period (Chen et al, 1993;Xie et al, 2006;Yao et al, 2008;Yuan et al, 2009b). The shelf break in the QDNB is located near the 200 m isobath, whereas the continental slope ranges between 200 and 2000 m (Wu et al, 1999).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Miocene and Late Oligocene stratigraphy of the Qiongdongnan basin have been only partially studied and documented (Yuan et al, 2009;Wu and Shi, 2005;Wei et al, 2001;Wang et al, 1998). By means of recent well and seismic data, more systemic and reliable information revealed the general and local stratigraphy characteristics of the basin.…”
Section: Stratigraphy Frameworkmentioning
confidence: 99%